Political battles over globalization and forging for the global citizenship - Ahmad, Rana Eijaz (Institute of Tun Dr. Mahathir Mohamad’s Thoughts,Universiti Utara Malaysia, 2010)
This is an age of communication; collectivism gives rise to global village that calls for a global citizenry. It is easy to be a globalectronic (global and electronic) citizen who attains his nationality through internet, multimedia extension, mobile phones, cyber space, and electronic mail etc. It is well-nigh impossible to be a global citizen as every individual has its idiosyncrasy that always grow up with the social milieu lying around him. Therefore, people living in the North are unable to cope with people living in the South in all aspects of life. Political unevenness between the North and the South is a major source of dichotomy between two poles. Globalization is a source that collects people in the form of a whole but ineffectual in forging them to be a global citizen. All political battles over globalization can become to an end if selective morality diminishes. The South is unable to move in the world at will but the North can. Hence claims of laissez faire, peace, human rights, good governance, and sustainable human development are at stake as pluralism facing crises in morality. Thus it seems difficult to have an end product in the form of a global citizenship. It is only possible when morality prevails in attaining its end product through freedom of expression, freedom of speech and freedom of association. This paper is based on inductive, deductive, and comparative methods of research.